Management of urticaria with Virechana: A case study - Poonam; Rishu Sharma; Sanjay Gupta; Deshraj Singh; Gyanendra Datta Shukla (Environment Conservation Journal, 2019)
In the present era due to over-industrialization and increase in pollution as well as changed life style, one can constantly meets with various pollutants; which ultimately results in weaken immune system and increased sensitivity toward allergens. This causes various types of allergic diseases. Urticaria is one of the most common allergic skin diseases characterized by erythematous and pruritic rashes. It affects 15-20% of the people at some point of their life. Highest incidence occurs at third decade of life. The discomfort and stress caused by urticarial can lead to serious impairment of quality life. In classics sheetpitta has almost similar symptomatology and causative factors as urticaria. In sheetpitta, vata and kapha are primarily disturbed and in combination of pitta they cause redness, swelling and itching on the skin. Although the diseases is not life-threatening, it makes the patient troubled due to its appearance, severe itching, and disturb the daily routine. In contemporary science there is no permanent cure, but only remission of the disease can be achieved by medicine. But these treatments can cause reoccurrence of the disease. So an effort has been made with Ayurvedic intervention. A male patient from Panchkarma OPD was treated with Virechana along with internal medication and dietary protocol. Significant relief in the symptoms is observed in the patient after Virechana and oral medication. Virechana may be better line of treatment for urticaria as it works on correcting the underlying root cause along with symptoms of the diseases.